Adaptation improvement using fuzzy logic - Huapaya, Constanza Raquel (2015)
A module of a Student Model in a Virtual Learning Environment will be presented in order to promote the personalization of instructional material based on the dynamic knowledge levels and learning styles. The improvement is provided by the inclusion experts' experience in the teaching field whose opinions have been expressed in fuzzy rules using two input linguistic variables (knowledge level and learning style) and two linguistic output variables (difficulty level and individual/group work). These last two variables categorize instructional materials.